Towards ubiquitous production systems and enterprises - Goran Putnik (2007)
In the evolvable manufacturing world we are moving towards systems made of small intelligent interacting units which make their own decisions independently from a centralized decision maker. System intelligence will be the collective intelligence resulting from a large number of individual decision, each one based on its local knowledge. In our paper we present the Ubiquitous Production Systems and Enterprises (UPSE) whose foundations can be found in two main scientific areas/disciplines, (1) Ubiquitous Computing Systems and (2) Virtual and Networked Enterprises and Organizations. We present the concept and the underlying formal model as well as our positioning in the state of the art of similar concepts. Finally we present some ongoing experiments that will work as a testbed for the UPSE concept.